The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1097/brs.0000000000001638
|View full text |Cite
|
Sign up to set email alerts
|

Posterolateral Fusion Versus Interbody Fusion for Degenerative Spondylolisthesis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 23 publications
0
18
1
Order By: Relevance
“…Autografts and allografts containing autologous bone marrow are routinely employed to stimulate osteogenesis either at the intervertebral space as in anterior lumbar interbody fusion (ALIF; Bohl et al, ) or at an ectopic site between two lumbar transverse processes bilaterally as in a posterolateral lumbar fusion (PLF; Liu, Wang, Qiu, Weng, & Yu, ). A variety of disorders may be treated with spinal fusion, including degenerative disc disease (DDD), spondylolisthesis, spinal stenosis, scoliosis, infections, spinal fractures and dystrophy, and various tumours (McAnany et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Autografts and allografts containing autologous bone marrow are routinely employed to stimulate osteogenesis either at the intervertebral space as in anterior lumbar interbody fusion (ALIF; Bohl et al, ) or at an ectopic site between two lumbar transverse processes bilaterally as in a posterolateral lumbar fusion (PLF; Liu, Wang, Qiu, Weng, & Yu, ). A variety of disorders may be treated with spinal fusion, including degenerative disc disease (DDD), spondylolisthesis, spinal stenosis, scoliosis, infections, spinal fractures and dystrophy, and various tumours (McAnany et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…2 This is of particular interest, as there is no robust data to support clinical superiority of adding interbody devices to instrumented posterior fusion. 10,15,31,32 It might be that this is being driven by the rise in popularity of minimally invasive surgery (MIS) that requires the interbody space for a surface area for fusion. Unfortunately, we cannot determine the percent of cases that were done with MIS techniques using the data sets employed here.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 If performing fusion, instrumentation has been accepted as a way to increase fusion success. 9,10 Interbody techniques have been suggested as ways to increase fusion success, potentially improve alignment, and/or allow for grafting with minimally invasive techniques. 10 However, there is debate on which fusion technique is best.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…McAnany et al conducted a meta-analysis of five prior studies, including 383 patients treated with a PLF and 268 treated with IBF [38]. It was concluded that there was no difference in rates of fusion, operative time, EBL, and ODI, SF-36, and VAS outcome measures between procedures.…”
Section: Interbody Fusionmentioning
confidence: 99%